1999
DOI: 10.1073/pnas.96.9.5101
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Darwin’s finches as revealed by mtDNA sequences

Abstract: Darwin's finches comprise a group of passerine birds first collected by Charles Darwin during his visit to the Galápagos Archipelago. The group, a textbook example of adaptive radiation (the diversification of a founding population into an array of species differentially adapted to diverse environmental niches), encompasses 14 currently recognized species, of which 13 live on the Galápagos Islands and one on the Cocos Island in the Pacific Ocean. Although Darwin's finches have been studied extensively by morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(156 citation statements)
references
References 28 publications
7
147
1
Order By: Relevance
“…AF489878-AF489903; Table 1) and previously published sequences (Hackett 1996: U15717, U15718; Burns 1997: AF006211-AF006258; Sato et al 1999: AF108772, AF108777, AF108790, AF108792, AF108796, AF108802, AF108806, AF108807; Lougheed et al 2000: AY005206, AY005218, AY005219, AY005220, AY005221; Sato et al 2001: AF310041-AF310043, AF310049, AF310053-AF310055) was used in this study. We focused our sampling on Sibley and Monroe's (1990) tanager-finches (tribe Thraupini) and included 91 individuals of 88 species representing the diversity seen within this group.…”
Section: Taxon Samplingmentioning
confidence: 84%
See 1 more Smart Citation
“…AF489878-AF489903; Table 1) and previously published sequences (Hackett 1996: U15717, U15718; Burns 1997: AF006211-AF006258; Sato et al 1999: AF108772, AF108777, AF108790, AF108792, AF108796, AF108802, AF108806, AF108807; Lougheed et al 2000: AY005206, AY005218, AY005219, AY005220, AY005221; Sato et al 2001: AF310041-AF310043, AF310049, AF310053-AF310055) was used in this study. We focused our sampling on Sibley and Monroe's (1990) tanager-finches (tribe Thraupini) and included 91 individuals of 88 species representing the diversity seen within this group.…”
Section: Taxon Samplingmentioning
confidence: 84%
“…Species that have been suggested include the Blue-black Grassquit (Volatinia jacarina) (Steadman 1982), other grassquits (genus Tiaris) (Sushkin 1925;Lowe 1936;Sato et al 1999;Sato et al 2001), seedeaters (genus Sporophila) (Salvin 1876;Ridgway 1897), 4 Nedra K. Klein is deceased.…”
mentioning
confidence: 99%
“…By contrast, several studies of radiation which post-date island formation have shown relatively rapid expansion and speciation, with a relatively short coalescence time within an archipelago. This can been seen among DarwinÕs finches (Freeland and Boag, 1999;Sato et al, 1999Sato et al, , 2001, as well as among birds of the Lesser Antilles (Hunt et al, 2001;. The western Indian Ocean sunbirds show elements of both patternsperiods of rapid expansion, as well as the colonization of new islands from older ones-reflecting the wide range of island ages in the region.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, fish flocks in lakes and complexes of finches on the Galápagos and Cocos Islands show overlap of intra-and interspecific divergence, and an absence of clustering of mtDNA lineages into speciesdiagnostic clades (Meyer etal. 1990;Meyer 1993;Strecker et al 1996;Parker & Kornfield 1997;Freeland & Boag 1999;Sato et al 1999).…”
Section: Discussionmentioning
confidence: 99%